The mediating role of academic self-efficacy in the influence of Thai sepak takraw coaches 'teaching style on athletes' learning engagement - Shihao Zhao; Wang, Lijun (Environment and Social Psychology, 2025)
This study aims to explore the relationship and mechanisms between the teaching style of Thai sepak takraw coaches and athletes 'learning engagement, and to examine the mediating role of academic self-efficacy. Method: The study employed questionnaires on teaching style, learning engagement, and academic self-efficacy to survey 900 athletes from three different schools. In the data analysis phase, SPSS27.0 software was used to systematically process and analyze the collected data. To further investigate the mediating effect of academic self-efficacy in the relationship between Thai sepak takraw coaches' teaching style and athletes 'learning engagement, AMOS28.0 software was used to construct a structural equation model, and the path mechanisms among variables were analyzed in detail using the Bootstrap method. Results: There is a significant correlation between teaching style, learning engagement, and academic self-efficacy. Direct effect analysis shows that teaching style has a significant direct predictive effect on athletes' learning engagement (β=0.500, P<0.001). Mediation effect analysis indicates that academic self-efficacy partially mediates the impact of teaching style on athletes 'learning engagement, with a mediation effect value of 0.212, and a 95% confidence interval of [0.144,0.239]. Conclusion: The teaching style of Thai sepak takraw coaches not only directly positively influences athletes' learning engagement but also indirectly affects it through academic self-efficacy.